2021
DOI: 10.17818/emip/2021/1.9
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Knowledge Transfer Performance at Universities

Abstract: Measuring the universities' knowledge transfer performance is important for both policymakers and universities due to the recognized social and economic impact of the knowledge transfer process. The aim of this paper is to investigate and discuss the contemporary knowledge transfer metrics used for measuring the knowledge transfer activities at universities. The research results show that the universities need to consider several important aspects when selecting and reporting on their knowledge transfer activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…The Strategy of Scientific Research Activity (2017-2021 defines the measures and instruments directed toward the higher quality of the research, access to modern technologies, and the promotion of a more competitive knowledge-based economy through the partnership between scientific research institutions and the private sector. One of the goals of the Strategy is to strengthen the collaboration between academia and industry through the following measures: improvement of the TT mechanisms, creation of a more favorable environment for innovative entrepreneurship, and provision of financial support to research and innovation (R&I) activities and entrepreneurship.…”
Section: Analysis Of the Legislative Framework Related To The Technol...mentioning
confidence: 99%
“…The Strategy of Scientific Research Activity (2017-2021 defines the measures and instruments directed toward the higher quality of the research, access to modern technologies, and the promotion of a more competitive knowledge-based economy through the partnership between scientific research institutions and the private sector. One of the goals of the Strategy is to strengthen the collaboration between academia and industry through the following measures: improvement of the TT mechanisms, creation of a more favorable environment for innovative entrepreneurship, and provision of financial support to research and innovation (R&I) activities and entrepreneurship.…”
Section: Analysis Of the Legislative Framework Related To The Technol...mentioning
confidence: 99%
“…Applying constructivist principles in learning models can effectively enhance college students' critical thinking ability [11]. Knowledge transfer is the influence of one kind of learning on another [12]. Using a questionnaire survey and experiment, Lee and Son (2021) [13] found that a significant increase in critical thinking can effectively improve learning transfer.…”
Section: Introductionmentioning
confidence: 99%
“…Previously published research has examined knowledge transfer in a variety of contexts (Dameri & Demartini, 2020;Greser et al, 2021;Haglund & Wåhlberg, 2015;Karanikić & Bezić, 2021;Kuciapski & Weichbroth, 2021;Tshuma, Steyn, & Van Waveren, 2018). However, there are few studies which have concentrated on the knowledge transfer of software project managers, despite the explosion of digital and software initiatives.…”
Section: Introductionmentioning
confidence: 99%